CORRELATION OF PARENTING STYLE AND INFECTIOUS DESEASE TOWARDS TODDLERS NUTRITIONAL STATUS IN SCAVENGER FAMILIES - Cut Dewi Sartika (Journal of Public Health Research and Community Health Development, 2021)
ABSTRACT The period of toodler (below five years old children) is very important; it is also a critical period which determines their future. Today, there are many children who have no adequate nutrients in their growth and development. The data in 2013 revealed that 17% or 98 million children in the developing countries underwent nutrition deficiency. The objective of the research was to find out the correlation of care pattern and infectious diseases with nutrition status of scavengers’ children at the Terjun Landfill, Medan Marelan Sub-district. The research used a survey method with cross sectional design. The samples were 84 toodlers at Lingkungan I, Kelurahan Paya Pasir. The variables were care pattern and infectious diseases. The data were analyzed by using chi square test. The result of the research showed that 45 children had good nutritional status, based on BB/U (Weight/Age), TB/U (Height/Age), and BB/TB (Weight/Height). Care pattern was assessed from three sub-variables: feeding pattern, health practice, and sanitation practice. All in all, the majority of the women had care pattern well, and there were two infectious diseases: diarrhea and ISPA (Acute Respiratory Tract Infection). The result of chi square test showed that there was no correlation between care pattern and toodler’s nutritional status, but there was the correlation between infectious diseases and their nutritional status (p=0.002). It is recommended that women not take their children to a landfill since children are vulnerable to infection. Hygiene and environmental sanitation should be promoted so that the respondent will be prevented from infectious diseases.Keywords: Balita, Care Pattern, Infectious Disease, Nutritional Status, Scavengers